E-learning lessons from the COVID-19 pandemic experience for built environment education in Zimbabwe - Chigara, B.; Moyo, T.; Gaule, B.; Nyamande, T. (South African Journal of Higher Education, 2025)
The COVID-19 pandemic and response efforts unprecedentedly disrupted social and economic activities worldwide. In the tertiary education sector, e-learning was embraced as a response during the pandemic. While this transition was important, learners in Zimbabwe experienced unprecedented challenges. This study investigates e-learning challenges and lessons for built environment education during the COVID-19 pandemic. A case study design was adopted wherein an online questionnaire was distributed and received from 471 built environment students of a selected public university in Zimbabwe. Descriptive and inferential statistics such as mean score (MS) and exploratory factor analysis were adopted for data analysis. Factor analysis revealed five (5) factors affecting a fruitful e-learning experience for built environment students: preparedness for e-learning, social interaction, technological and infrastructure issues, work ethic and e-learning literacy issues, and online class size and student attendance. The study highlights the importance of adopting policy interventions to promote economy to access data, acquire information communication technology (ICT) gadgets, and use interactive online platforms that encourage learner-to-learner and learner-to-instructor engagement. Considering that the study is based on the views of students from one institution of higher learning, caution should be exercised when generalising the results to other universities.